Peramalan Jumlah Penumpang Travel dengan Metode Triple Exponential Smoothing (Kasus Day Trans Tour dan Travel Kota Semarang) - Winarsih, Dewi; Nugroho, Adi (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
Tour and travel services are currently quite influential in the community, because they help people travel. because sometimes passengers can get on or off without warning. So that tour and travel entrepreneurs can anticipate the decline in passengers by introducing marketing, city destination routes, tour packages, cars, drivers, and other services for the convenience of passengers. Triple Exponential Smoothing is a forecasting method that has the capacity to manage seasonal elements and trends that are simultaneously present in the time series data. Normalization Results of the SSE Method SEE Values 1198921.0732 MSE 47956.8429 MAPE 218.9905. Triple Exponential Smoothing Using the parameters of the α, β, and γ methods that are best for the TES method on RStudio, an accuracy value consisting of SSE, MSE, and MAPE will be generated. Mar 666.0032 Apr 367.7103 May 377.8220. The MAPE approach yields the largest percentage of accurate predictions.